Academic Integrity and Student Mental Well-Being: A Rapid Review - Eaton, Sarah Elaine; Pethrick, Helen; Turner, Kristal Louise (Canadian Perspectives on Academic Integrity, 2023)
Despite concerns arising from academic integrity practitioners, researchers, and stakeholders about the relationship between academic integrity (or violations of academic integrity) and student mental well-being (or distress), there is a lack of literature synthesizing available evidence. Particularly, it is unclear about when student mental well-being may be of concern during procedures that concern breaches of academic integrity. Our rapid review identified and analysed scholarly sources (n = 46) to understand the relationship between academic integrity and mental well-being among postsecondary students. Five themes emerged: a) negativity bias; b) inconsistency of definitions; c) paradigmatic tensions; d) focus on external stressors; and e) focus on mental health prior to a critical incident. We propose several calls to action and implications for practice. There is a need to better understand the impact of an alleged or actual academic integrity violation on students’ mental well-being. Practitioners should integrate supports for students’ mental well-being in processes and procedures that uphold academic integrity.